The Influence of Competence and Cooperation on Principal Performance with School Culture as a Moderator - Istichomahwati; Muhammad Khafid (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of principal competency and collaboration on school performance with school culture as a moderating variable in Mlonggo District, Jepara. This research applies a quantitative explanatory approach, using survey methods and questionnaires to collect data from 52 school principals selected through purposive sampling. Data analysis employed multiple linear regression and moderation analysis to test the proposed hypotheses. The findings indicate that principal competency and collaboration have a significant positive effect on principal performance, both directly and through school culture. School culture was found to strengthen the impact of competency and collaboration on performance, highlighting its critical role in creating a conducive and effective educational environment. Simultaneously, the combined influence of competency, collaboration, and school culture shows a moderate positive relationship with principal performance. The study provides empirical evidence that enhancing principal competency, fostering effective collaboration, and cultivating a strong school culture are essential strategies to improve educational leadership and overall school performance.